Prevalence and associated factors of foot self-care practice among diabetic patients in Africa: systematic review and meta-analysis - Atalay, Yibeltal Assefa; Alemie, Bersufekad Wubie; Gelaw, Kelemu Abebe (Frontiers in Endocrinology, 2025)
IntroductionNowadays, diabetes mellitus is a major global health issue with serious social, economic, and developmental impacts. One of its most severe complications is foot problems. Research shows that poor self-care practices in managing diabetic feet are a key factor in ulcer development.ObjectiveThis study aimed to determine the pooled prevalence of foot self-care practice and associated factors among diabetic patients in Africa.MethodsWe found articles using electronic databases, including PubMed, Cochrane Library, Google Scholar, Web of Science, African Journals Online, and Science Direct. Accordingly, we identified 143 published articles. A total of 31 eligible studies were included in the systematic review. Data extraction used a standardized checklist, and analysis was conducted with STATA 14 statistical software. Various methods were used to assess the presence of publication bias, including funnel plots and the Begg and Egger regression test. A significance level of P ≤0.05 was used to indicate potential publication bias. Heterogeneity between included studies was assessed using the I2 statistics. The random effect model was used to estimate the pooled estimates.ResultsThe pooled prevalence of foot self-care practices among diabetic patients in Africa was 46.93% (95%CI (39.44–54.41)). Diabetic foot self-care practices were significantly associated with rural residence (AOR: 2.50, 95% CI (1.65–3.80)), educational level (AOR: 3.00, 95%CI (2.07–4.34)), and knowledge level of diabetes patients (AOR: 3.41, 95%CI (2.22–5.23)).ConclusionsIn conclusion, more than half of diabetic patients had poor diabetes foot self-care practices. Diabetic foot self-care practice was associated with a level of education, rural residence, and the knowledge level of diabetic foot care. Therefore, intervention programs ought to prioritize enhancing the knowledge base of individuals with diabetes to promote better self-care practices for their feet.